The influence of psychological captial and classroom management on teachers well-being: A case study among English university teacher in Zhejiang Province, China / Wu Yong - Wu , Yong (2020)
This study aims to investigate the associations among EFL teachers’ psychological capital, well-being (PERMA), and their College English classroom management in Chinese universities of Zhejiang province. This study is a non-experimental quantitative research which used a questionnaire to collect data. comprised four sections: teachers’ demographics, psychological capital, well-being (PERMA) and EFL classroom management. A total of 486 EFL teachers from 19 universities in Zhejiang province, China, were randomly selected. Following the filtering of data which involved the missing data, normality, outliers and multicollinearity issues, only 478 samples were found suitable for analysis. The descriptive statistics analysis derived from this study showed the levels of the EFL teachers’ psychological capital, well-being (PERMA), and their College English classroom management in terms of means and standard deviation. The findings indicated that the Chinese university College English EFL teachers in Zhejiang province had perceived that they have a high level of psychological capital, a high level of well-being (PERMA), and a high level of EFL classroom management. Inferential statistics such as the Person Product-Moment analysis was used to identify the correlations between the variables. The results showed that there were statistically significant positive correlations between psychological capital, well-being (PERMA) and EFL classroom management.Additionally, the multiple regression analysis showed that the Hope dimension of psychological capital was statistically significant predictor of College English classroom management while the Optimism dimension of psychological capital was a significant predictor of well-being (PERMA).This study also used structural equation modelling (SEM) procedures with AMOS to examine the mediation, and the moderation model proposed. The results revealed that there was a partial positive mediating effect of the EFL teachers’ well-being (PERMA) on the relationship between the EFL teachers’ psychological capital, and their EFL classroom management. The moderating effect test indicated that the EFL teachers’ working experience was a significant moderator on the relationship between the EFL teachers’ psychological capital, and their classroom management. This study makes significant contributions to the general body of knowledge in foreign language education, second language acquisition, teachers’ development as well as the psychology field. It had successfully integrated positive psychology into the field of second language teaching.